Yield and Physicochemical Characteristics of Kaffir Lime Leaf Essential Oils Subjected to Different Post-Harvest Treatment - Budiarto, Rahmat; Poerwanto, Roedhy; Santosa, Edi; Efendi, Darda; Agusta, Andria; Rofiq, Muhamad Abdul (Journal of Tropical Crop Science, 2024)
The importance of kaffir lime leaf as essential oils (EOs) raw material is starting to get attention because of its commercial value; however, there is no quality reference for kaffir lime leaf EOs, especially in response to various post-harvest handlings. This study aimed to describe the physicochemical characteristics and yield of kaffir lime EOs subjected to different post-harvest. Bogor originated-kaffir lime leaf was prepared to be subjected to several post-harvest treatments, i.e., control/fresh green leaves (P1); milling to produce green leaf flour (P2); drying to produce dry brown leaf (P3), and milling and drying to produce brown leaf flour (P4). The result showed that post-harvest treatment generally decreases an oil yield and increases darkness color, specific gravity and refractive index of tested EOs. Additionally, post-harvest treatment also changes metabolite profile revealed by GCMS analysis. The relative percentage of caryophyllene and citronellol tends to increase, while the linalool and citronellal levels decrease due to tested post-harvest treatment. It was implied that for the benefit of the fragrance industry with a high citronellal requirement, EOs should be made from fresh green leaves and the leaves should be avoided from drying and powdering treatment.